2012
DOI: 10.1038/ng.2427
|View full text |Cite
|
Sign up to set email alerts
|

Variation in germline mtDNA heteroplasmy is determined prenatally but modified during subsequent transmission

Abstract: A genetic bottleneck explains the marked changes in mitochondrial DNA (mtDNA) heteroplasmy observed during the transmission of pathogenic mutations, but the precise timing remains controversial, and it is not clear whether selection plays a role. These issues are critically important for the genetic counseling of prospective mothers, and developing treatments aimed at disease prevention. By studying mice transmitting a heteroplasmic single base-pair deletion in the mitochondrial tRNAMet gene, we show that mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
135
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(151 citation statements)
references
References 22 publications
6
135
0
10
Order By: Relevance
“…This ES cell shift was suggested to be the result of strong mtDNA bottleneck occurring upon epiblast specification in the few cells directed to somatic lineages. After ES cell stage, mtDNA heteroplasmy levels did not vary considerably between different ES cell clones or in different solid tissues in primates, whereas in oocytes mtDNA segregation appeared to be random in mice and monkeys (25,46). As previously suggested that reprogramming takes iPSC mitochondria back to an epiblast-like stage (31, 49), our results further suggest that also the mtDNA bottleneck is reproduced in vitro during reprogramming.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…This ES cell shift was suggested to be the result of strong mtDNA bottleneck occurring upon epiblast specification in the few cells directed to somatic lineages. After ES cell stage, mtDNA heteroplasmy levels did not vary considerably between different ES cell clones or in different solid tissues in primates, whereas in oocytes mtDNA segregation appeared to be random in mice and monkeys (25,46). As previously suggested that reprogramming takes iPSC mitochondria back to an epiblast-like stage (31, 49), our results further suggest that also the mtDNA bottleneck is reproduced in vitro during reprogramming.…”
Section: Discussionsupporting
confidence: 69%
“…This phenomenon could be explained by the existence of mitochondrial genetic bottleneck (42,43), involving decreased mtDNA copy number, selective amplification of a subset of mtDNA molecules, or preferential amplification of an mtDNA type. However, the exact stage in embryogenesis when this bottleneck occurs has been under debate (25,34,47,48). The biphasic shift in our iPSCs mimics closely the results seen in primate heteroplasmic ES cells, which had shifted toward homoplasmy at early passage (46).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The mtDNA mutator mouse demonstrated the differential purification between synonymous and nonsynonymous mtDNA variants within the mouse germline (Stewart et al 2008). Moreover, the extent of heteroplasmy was primarily determined in the oocyte population with the level of mtDNA variant modified in the next generation (Freyer et al 2012). Oocyte metabolism could cope with slightly inefficient OXPHOS and, because of the mitochondrial genetic bottleneck in the germline (Cree et al 2008), different levels of mtDNA variants can be found among the oocyte population (Frederiksen et al 2006).…”
Section: Discussionmentioning
confidence: 99%